Now You See It, Now You Don't!—Spontaneous Complete Necrosis and Reappearance of Hepatocellular Carcinoma - Baby, Akhil; Suryavanshi, Shubham; Philips, Cyriac Abby; Ooommen, Tharun Tom; Augustine, Philip; Rajesh, Sasidharan (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Spontaneous regression of hepatocellular carcinoma (HCC) is a rare phenomenon caused by complex multifactorial mechanisms. We report the case of a 76-year-old male with a history of chronic liver disease and HCC who experienced complete spontaneous tumor regression followed by recurrence. The regression may have been triggered by ischemia from portal vein thrombosis and systemic inflammation. Key mechanisms behind spontaneous regression include tumor hypoxia and immune responses. This case highlights the complexity of spontaneous regression and its potential role in developing novel cancer therapies.
Keywords: ischemia; hypoxia; cirrhosis; thrombus; cytokine; immune